Black Americans suppress emotions when prejudice is believed to stem from shared ignorance - Chaney, Kimberly E.; Pham, Minh Duc; Cipollina, Rebecca (Frontiers in Psychology, 2024)
Past research examining lay theories of the origins of prejudice has focused on White Americans and has not considered how Black Americans' lay theories of prejudice may impact emotion regulation following discrimination. Across three samples of Black Americans (N = 419), the present research examined relationships between endorsement of two lay theories of prejudice origins (1, beliefs that prejudice stems from shared social ignorance and 2, that prejudice stems from malice). Stronger beliefs that prejudice stems from shared ignorance were associated with greater expression suppression following experiences of racial discrimination (Studies 1b, 2), which was in turn associated with psychological distress (Study 2). By centering the beliefs and experiences of Black Americans in response to discrimination events, the present research has implications for understanding how emotion regulation following racial discrimination is impacted by marginalized groups' conceptualizations of prejudice. Future research should investigate how these factors impact health disparities.